2018
DOI: 10.1016/j.appet.2017.10.043
|View full text |Cite
|
Sign up to set email alerts
|

Attachment and eating: A meta-analytic review of the relevance of attachment for unhealthy and healthy eating behaviors in the general population

Abstract: Attachment relationships play an important role in people's wellbeing and affliction with physical and mental illnesses, including eating disorders. Seven reviews from the clinical field have consistently shown that higher attachment insecurity-failure to form trusting and reliable relationships with others-systematically characterized individuals with eating disorders. Nevertheless, to date, it is unclear whether (and if so how) these findings apply to the population at large. Consequently, the objective of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
101
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 113 publications
(118 citation statements)
references
References 158 publications
(211 reference statements)
10
101
6
1
Order By: Relevance
“…Overall, the results indicated that better attachment to mother prospectively predicted less pronounced disordered eating among girls and boys, as pointed out by other authors (Jewell et al, 2016;Ward, Ramsay, & Treasure, 2000). However, in contrast to a recent meta-analysis which did not find any differences regarding the attachment figure (Faber et al, 2018), our results underline the differential role that fathers and This study supported the protective influence of a better attachment towards mother on disordered eating in both genders, thus extending previous cross-sectional evidence (Bäck, 2011;Boone, 2013). Our results parallel some prospective studies showing that less secure attachment to mother predicted increases in ED symptoms (Burge et al, 1997;Goossens et al, 2012).…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…Overall, the results indicated that better attachment to mother prospectively predicted less pronounced disordered eating among girls and boys, as pointed out by other authors (Jewell et al, 2016;Ward, Ramsay, & Treasure, 2000). However, in contrast to a recent meta-analysis which did not find any differences regarding the attachment figure (Faber et al, 2018), our results underline the differential role that fathers and This study supported the protective influence of a better attachment towards mother on disordered eating in both genders, thus extending previous cross-sectional evidence (Bäck, 2011;Boone, 2013). Our results parallel some prospective studies showing that less secure attachment to mother predicted increases in ED symptoms (Burge et al, 1997;Goossens et al, 2012).…”
Section: Discussionsupporting
confidence: 61%
“…Our findings suggest that building secure attachment relationships with parents may prevent the emergence of unhealthy eating behaviors in adolescents (Faber et al, 2018). Our findings suggest that building secure attachment relationships with parents may prevent the emergence of unhealthy eating behaviors in adolescents (Faber et al, 2018).…”
Section: Implications For Research and Practicementioning
confidence: 57%
See 2 more Smart Citations
“…According to van Strien et al [41], high overconsumers are usually overweighted, have higher degrees of dietary restraint and also higher degrees of emotional and of external eating. They are also more often female and better educated.…”
Section: Discussionmentioning
confidence: 99%